Fax modem system analysis in concept, design & implementation using VHDL / Zuliana Zakaria - Zuliana, Zakaria (2003)
This graduation project is entitled Designing Fax Modem using VHDL. This project is indeed the starting point the way of exploring secret of embedded system. It is actually a practice with the knowledge and hardware and software in computer organization and design. At first stage architecture of fax modem will be analyzed and studied. Then the architecture of the modem is redesigned using hardware prototyping. The hardware prototyping is method that used to test and evaluate the design of a particular fax modem. Coding or programming with VHSIC Hardware Description Language (VHDL) undertakes this approach. Finally, the completed programs and codes will be simulated using the Xilinx Foundation Software. This report is a description of analysis and design of the modem. For the implementation and simulation it will conducted continuously from this stage. This report including books web pages articles. The implication of this report is the understanding of the hierarchical and parallel nature of the fax modem that is the most important thing in order to design processor.